Association between The Study of Nerve Conductivity and The Medianus Nerve Cross-Sectional Area in Carpal Tunnel Syndrome - Ninik Dwiastuti1 , Meisy Andriana1 , Mei Wulan1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Carpal tunnel syndrome (CTS) is a collection of symptoms caused by clasps on mediannerve. CTS diagnosis is based on anamnesis, physical examination and investigation. Medianus nerveelectrodiagnostic examination is the gold standard of CTS diagnosis.Objective: To determine the association between the study of nerve conductivity measured byelectrodiagnostic and the median nerve cross-sectional area measured by musculoskeletal USG in CTSpatients.Methods: This study was conducted at medical rehabilitation installation of Dr. Soetomo Teaching HospitalSurabaya, Indonesia. The samples were 15 hand that obtained from 13 females with CTS.Results: The Pearson Association analysis showed a significant positive correlation between the the crosssectional area and the motor distal latency of medianus nerve (r = 0.625; p = 0.013). There was no significantcorrelation between the cross-sectional area with sensory distal latency, sensory amplitude, motor amplitude,sensory nerve conductivity velocity and motor nerve conductivity velocity of median nerve.Conclusion: Electrodiagnostic and musculoskeletal USG have different roles in the diagnosis of CTS.Electrodiagnostics as the gold standard provided information about the level and severity of lesions n.Medianus. Musculoskeletal ultrasound could be used as an additional examination that provided informationon the anatomy of median nerve and other structures located in the carpal tunnel.